Construction law : an introduction for engineers, architects, and contractors - Kelley, Gail S. (Hoboken, N.J. : John Wiley & Sons, 2012)
For a construction business to function properly, architects, engineers, and contractors need to understand how the various state and federal laws affect their business and how to avoid disputes and exposure to liability. This book offers a comprehensive review of the US legal environment, both criminal and civil, focusing on the key legal concepts and issues applicable to a typical construction project. Construction professionals will find clear, concise introduction to a wide range of contractual issues related to project participants, as well as issues related to the actual construction and.
5.9: Third-Party Beneficiaries.
Includes index.
This edition in English.
Print version record and CIP data provided by publisher.
Keywords: Construction contracts -- United States; Construction industry -- Law and legislation -- United States; Construction contracts -- United States; Construction industry -- Law and legislation -- United States; LAW -- Taxation; Construction contracts; Construction industry -- Law and legislation; United States; Electronic books; Electronic books